Experimental Observation of the Coupling of a Nonlinear Wave to a Topological Edge State - Bisianov, Arstan; Kremer, Mark; Wimmer, Martin; Szameit, Alexander; Peschel, Ulf (2018 Conference on Lasers and Electro-Optics, CLEO 2018 - Proceedings, 2018)
We experimentally investigate a topologically non-trivial edge state of the SSH model. In the presence of nonlinearity topological protection breaks down resulting in efficient energy transfer from a nonlinear wave to the edge state.
CRIS-Team Scopus Importer:2023-04-20